Beautiful Creatures (Yen Press, 2013)
In a graphic novel adaptation of the book, sixteen-year-old Ethan is powerfully drawn to Lena, a new classmate with whom he shares a psychic connection and whose family hides a dark secret that may be revealed on her sixteenth birthday.